1977
DOI: 10.1159/000260271
|View full text |Cite
|
Sign up to set email alerts
|

Buffering Capacity in Human Dental Plaque Fluid

Abstract: The buffering capacity was determined in the extracellular aqueous phase of 24-hour plaque samples obtained from dental students. The mean pH of five control samples of plaque fluid was 6.54 ± 0.26 SD. In the range pH 6–5, the mean buffering capacity was 3.2 × 10––4 mol ΔaH+/mol H+ added while in the range pH 5–4 it was 1.8 × 10––3 mol ΔaH+/mol H+ added, indicating a reduction in buffering at the lower pH range. Buffering between pH 5 and pH 4 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

1979
1979
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 8 publications
4
6
0
Order By: Relevance
“…Clearly, the calculated titration curve is in reasonable agreement with the experimental points; consequently, most of the buffer capacity of the PF is here ascribed to the presence of carboxylic anions. The buffer capacity of the PF in the titration range, expressed as the number of moles of strong acid required to lower the pH value from 5.0 to 4.0, was 12.8 nmol of H+/mg wet plaque weight, assuming PF to be 35% of the wet plaque weight (Jenkins, 1966;Edgar and Tatevossian, 1971); this is in good agreement with the value reported by Tatevossian (1977). The correspondence between the experimental points and the calculated curve, shown in Fig.…”
Section: Methodssupporting
confidence: 86%
See 2 more Smart Citations
“…Clearly, the calculated titration curve is in reasonable agreement with the experimental points; consequently, most of the buffer capacity of the PF is here ascribed to the presence of carboxylic anions. The buffer capacity of the PF in the titration range, expressed as the number of moles of strong acid required to lower the pH value from 5.0 to 4.0, was 12.8 nmol of H+/mg wet plaque weight, assuming PF to be 35% of the wet plaque weight (Jenkins, 1966;Edgar and Tatevossian, 1971); this is in good agreement with the value reported by Tatevossian (1977). The correspondence between the experimental points and the calculated curve, shown in Fig.…”
Section: Methodssupporting
confidence: 86%
“…The correspondence between the experimental points and the calculated curve, shown in Fig. 2, does not preclude the contribution of other constituents, such as proteins and polyamines, known to exist in the PF (Tatevossian and Newbrun, 1981;Vratsanos and Mandel, 1985); in this respect, we observed that the fluid became cloudy at a pH value of 4.38, most probably due to the precipitation of proteins, as suggested by other investigators (Tatevossian, 1977). Nevertheless, the contribution of other constituents, different from the organic acids, to the buffer capacity of the PF appears to be minor.…”
Section: Methodssupporting
confidence: 85%
See 1 more Smart Citation
“…This is the pattern we observed by titration (Shellis and Dibdin, 1988); Tatevossian (1977) and Margolis et al (1988) have recorded similarly shaped acid titration profiles between the initial pH and pH 4. Since the data of Carey et al cover a restricted pH range, little can be deduced from their data about the buffering/pH profile.…”
Section: Curve Iv)supporting
confidence: 83%
“…For this reason, the sodium salts of the solutes were used throughout this series. Variations in the degree of dissociation of these solutes in plaque fluid at pH 6.5 ± 0.3 [Tatevossian, 1977] appear not to be the relevant factor in these studies.…”
Section: Discussionmentioning
confidence: 63%